2022
DOI: 10.3390/agronomy12020271
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic Practices to Increase the Yield and Quality of Common Bean (Phaseolus vulgaris L.): A Systematic Review

Abstract: Common bean (Phaseolus vulgaris L.) is the most important legume for human consumption worldwide and an important source of vegetable protein, minerals, antioxidants, and bioactive compounds. The N2-fixation capacity of this crop reduces its demand for synthetic N fertilizer application to increase yield and quality. Fertilization, yield, and quality of common bean may be optimised by several other agronomic practices such as irrigation, rhizobia application, sowing density, etc. Taking this into consideration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 211 publications
1
24
0
2
Order By: Relevance
“…Increasing plant systemic immunity is an eco-friendly and more effective approach for plant viral control. Plant growth-promoting rhizobacteria (PGPR) have improved plant growth under various biotic and abiotic stresses ( Al-Ani and Adhab, 2013 ; Karavidas et al, 2022 ; Rizvi et al, 2022 ). The PGPRs produce a wide range of bioactive chemicals that could induce the plant systemic resistance by activating many plant protection genes against viruses and/or enhancing the plant growth for better nutrient and water acquisition ( Vejan et al, 2016 ; Abdelkhalek et al, 2020a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing plant systemic immunity is an eco-friendly and more effective approach for plant viral control. Plant growth-promoting rhizobacteria (PGPR) have improved plant growth under various biotic and abiotic stresses ( Al-Ani and Adhab, 2013 ; Karavidas et al, 2022 ; Rizvi et al, 2022 ). The PGPRs produce a wide range of bioactive chemicals that could induce the plant systemic resistance by activating many plant protection genes against viruses and/or enhancing the plant growth for better nutrient and water acquisition ( Vejan et al, 2016 ; Abdelkhalek et al, 2020a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…For the rural poor in eastern and southern Africa, common beans provide nutritional benefits to the cereal-dominated diet as beans are a cheap source of proteins and essential minerals (Monyo and Kananji, 2013;Nchimbi-Ms and Tryphone, 2010). A systematic review by Karavidas et al (2022) established that most bean yield studies focused on breeding, irrigation and rhizobia treatment with effects of fertilisation (mostly inorganic fertilisers) and intercropping accounted for in 11 and 5% of the 250 sources reviewed, respectively. Most bean-maize intercrops are with climbing beans due to their canopy advantage, but a recent study by Nkhata et al (2021) in Malawi found higher intercropping efficiencies for dwarf bean genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…The low productivity has been attributed to declining soil fertility, use of unimproved genotypes, non-use of good agronomic practices, climate variability, and increase in incidence and severity of pests and diseases (Beebe et al, 2013;Monyo and Kananji, 2013;Mugendi et al, 2011;Wortmann et al, 1998). The use of improved genotypes is considered as a principal tool to optimise the productivity of common bean (Karavidas et al, 2022), but about 70% of farmers in Malawi use local genotypes (Katungi et al, 2012) and up to 90% of those using improved genotypes rely on recycled seed from local seed systems (Maereka and Rubyogo, 2020). However, access to improved bean genotypes has also proved to be a problem in SSA, including Malawi.…”
Section: Introductionmentioning
confidence: 99%
“…Práticas agronômicas de base biológica para a produção primária, oferecendo um impacto mais positivo nas funções ecológicas e na sustentabilidade econômica, também são excelentes estratégias para alcançar os Objetivos de Desenvolvimento Sustentável das Nações Unidas (ODS da ONU), ou seja, limitar a desnutrição e alcançar a segurança alimentar. Tais práticas podem preservar os recursos naturais, reduzir os custos de manejo das culturas na agricultura (Karavidas et al, 2022).…”
Section: Introductionunclassified
“…Práticas como consórcio de culturas, agricultura orgânica e sistema de plantio direto são algumas das práticas agronômicas sustentáveis mais importantes, com aplicações que resultaram no aumento da biodiversidade do solo e na melhoria da estrutura e conservação do solo (Karavidas et al, 2022). A implantação de sistemas de manejo conservacionistas como o plantio direto trazem inúmeros benefícios no tocante à conservação dos recursos naturais, ao priorizar a manutenção de resíduos vegetais na superfície e reduzir a movimentação do solo.…”
Section: Introductionunclassified